ChemInform Abstract: Soft Matter Approaches for Enhancing the Catalytic Capabilities of Polyoxometalate Clusters. Issue 24 (2nd June 2014) - Zhang, Baofang; Yin, Panchao; Haso, Fadi; Hu, Lang; Liu, Tianbo
Abstract Review: 52 refs.